2002
DOI: 10.1007/s00467-002-0905-3
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous improvement of hypertension in multicystic dysplastic kidney: a case report

Abstract: We report a case of transitory hypertension associated with unilateral multicystic dysplastic kidney (MCDK). A newborn girl with MCDK, detected by prenatal ultrasonography, was conservatively treated and has been followed for 18 months at the Pediatric Nephrourology Unit (HC-Belo Horizonte, Brazil). Arterial hypertension was observed at about 4 months of age and was associated with high levels of plasma renin activity and circulating angiotensin, and also with changes in renal Doppler ultrasonography. For thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
3
17
0
2
Order By: Relevance
“…6 After extensive literature review, we found only 19 cases of systemic hypertension associated with MDK. 13 In our patient population, as with several studies, there was no report of malignant transformation of MDK. This is a possible complication that has been sporadically described.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…6 After extensive literature review, we found only 19 cases of systemic hypertension associated with MDK. 13 In our patient population, as with several studies, there was no report of malignant transformation of MDK. This is a possible complication that has been sporadically described.…”
Section: Discussionsupporting
confidence: 68%
“…The incidence of complications was negligible, only one patient had high blood pressure caused by MDK, with spontaneous resolution. 13 Serial ultrasound exams revealed involution of MDK in 48 (90%) cases, of which nine (17%) units became undetectable during the follow-up. After the sixth year of life, all the affected renal units were below the 5th percentile of the renal length expected for age.…”
Section: Discussionmentioning
confidence: 94%
“…Não houve necessidade de remoção cirúrgica do RDM durante o período de seguimento. A incidência de complicações foi pequena; apenas uma paciente apresentou elevação da pressão arterial atribuída ao RDM, com melhora espontânea 13 . Os exames ultra-sonográficos seriados mostraram involução do RDM em 48 (90%) casos, sendo que nove (17%) unidades se tornaram indetectáveis no transcorrer do seguimento.…”
Section: Discussionunclassified
“…Apenas no estudo multicêntrico realizado na Alemanha foram relatados cinco casos (2,5%) de hipertensão arterial em 204 crianças acompanhadas 6 . Após extensa revisão da literatura, encontramos apenas 19 casos de hipertensão arterial sistêmica associada com RDM 13 . Em nossa casuística, assim como nas várias séries publicadas, não houve relato de transformação maligna do RDM.…”
Section: Discussionunclassified
“…Some smaller studies of patients born with solitary functioning kidneys conclude that these individuals are at risk of hypertension later in life, from hyperfiltration and/or elevated renin activity [38][39][40][41]. Furthermore, case reports have described how MCDK patients with hypertension were cured by nephrectomy of the affected kidney [42][43][44].…”
Section: Blood Pressurementioning
confidence: 94%